Phase stability and magnetic behavior of FeCrCoNiGe high-entropy alloy - Huang, Shuo; Vida, Ádám; Molnár, Dávid; Kádas, Krisztina; Varga, Lajos Károly; Holmström, Erik; Vitos, Levente (Applied physics letters, 2015)
We report an alternative FeCrCoNiGe magnetic material based on FeCrCoNi high-entropy alloy with Curie point far below the room temperature. Investigations are done using first-principles calculations and key experimental measurements. Results show that the equimolar FeCrCoNiGe system is decomposed into a mixture of face-centered cubic and body-centered cubic solid solution phases. The increased stability of the ferromagnetic order in the as-cast FeCrCoNiGe composite, with measured Curie temperature of 640 K, is explained using the exchange interactions.